HUBUNGAN ANTARA DUKUNGAN SUAMI DAN FREKUENSI KUNJUNGAN ANTENATAl TERHADAP TINGKAT KECEMASAN PADA IBU HAMIL TRIMESTER III DI PMB FERAWATI TAHUN 2024 - Adhish Pramudita; Rohani; Gustiani, Ria; Dwi Treasa, Adisty (Jurnal Kesehatan dan Pembangunan, 2025)
Anxiety and worry during pregnancy are an inevitable occurrence, almost always accompany pregnancy and are part of a normal adjustment process to the physical and psychological changes that occur during pregnancy (Elsera et al. 2022). Impact Anxiety of pregnant women will affect the baby's birth weight, Stress during pregnancy can cause low birth weight for gestational age, early delivery, hypertension, and changes in physical outcomes such as increased risk of asthma. In addition, it can also have an impact on the growth and development of children's nervous systems (Magister et al. 2020). Purpose of the Study To determine the relationship between husband support and frequency of antenatal visits on the level of anxiety in pregnant women in the third trimester. The results of the study obtained a p value = 0.038 < ? (0.05), this shows that there is a significant relationship between the Relationship of Husband Support and the Level of Anxiety of Pregnant Women at PMB Vitri Suzanti Palembang. Meanwhile, the relationship between the frequency of antenatal visits and the level of anxiety was obtained with a p value = 0.038 < ? (0.05), this shows that there is a significant relationship. Recommended for future researchers Can conduct similar studies using more samples, using different research methods and finding out more about the relationship between husband support and frequency of antenatal visits on anxiety levels in third trimester pregnant women.